Basic pathogenic mechanisms of atherosclerosis. Issue 1 (1st January 2020) - Alfarisi, Hamad Abdulsalam Hamad; Mohamed, Zenab B. Hamad; Ibrahim, Muhammad Bin
ABSTRACT: Atherosclerosis is a chronic inflammatory disease of the inner wall of large- and medium-sized arteries. It is a disease of multiple causes which regarded as the primary underlying cause of heart diseases and cerebrovascular accidents. Pathologically, atherosclerosis is a chronic arterial inflammation secondary to prolonged exposure to oxidative stressors and involves multiple cell types and cellular mediators. Oxidized lipids derived from low-density lipoprotein contribute to multiple stages of atherosclerotic plaque development and progression through production of inflammatory cytokines. Diet and dietary habits are the major driving forces for development and modification of atherosclerotic diseases. Genetics and epigenetics have a significant influence on development and progression of atherosclerosis. Future therapeutic options may target the pathogenic mediators of atherosclerosis at multiple molecular levels.